Ideal Arrangements for Fines to Enhance Legal Awareness and Minimize Waste Effectively in Society - Rauf, Abdusalam; U. Puluhulawa, Fenty; Ahmad, Ahmad (Estudiante Law Journal, 2024)
The implementation of fines as a legal instrument plays a crucial role in shaping public behavior concerning waste management. Despite the existence of numerous regulations governing waste management, the effectiveness of imposing fines remains limited in raising legal awareness and reducing waste volume in society. This study aims to explore the ideal framework for implementing fines to enhance legal awareness and minimize waste, emphasizing more effective and systematic law enforcement. Utilizing a normative juridical and sociological approach, the study analyzes existing regulations and identifies obstacles in the application of fines in Indonesia. The findings reveal that while fines have the potential to reduce waste, the main challenges include insufficient public education, weak law enforcement, and inconsistencies between the amount of fines imposed and their intended deterrent effects. The study recommends strengthening waste management regulations, increasing community participation, and implementing proportional fines coupled with stringent monitoring systems to achieve significant waste reduction. With a more ideal regulatory framework, it is hoped that public legal awareness will improve, paving the way for sustainable waste management practices.